Formation of Professionally Oriented Linguistic Identity in a Multilingual Environment - Zhusupova Р.Ф.; Niyazova А.Е.; Abduova Б.С. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
One of the pressing issues of the modern educational system is the development of new theoretical approaches and advanced paradigms. One of the important problems is the development and improvement of principles of multilingual education in traning future professionals who are professionally competent in different languages. For this purpose there is a linguistic methodological modeling of a new type of a professionally linguistic personality. The transfer of language and speech achievements in the native Russian or Kazakh and English languages with the escape from one language code into another will lead to the formation of a linguistic personality who possesses different languages skills